Interactive 3D multimedia learning tool in biology - skeleton (MLTB-S) / Amirrudin Kamsin, Zaid Zainal and Mohd Yusof Abdullah - Kamsin, Amirrudin; Zainal, Zaid; Abdullah, Mohd Yusof (2006)
Nowadays, as biology has been taught at schools for years, the teachers have been facing a problem on how to get the students to fully understand the human biology. Of course a student can explain what a skull is, based on the books that he or she has read, but does he or she truly know what a skull looks like. Has he or she touched one? Examine it closely. And not only that, the current method of teaching biology is too static and boring. The teachers teach, and the students listen to it. There has to be some way to change this. The learning tool that has been developed here is called "Interactive 3D Multimedia Learning Tool in Biology - Skeleton ", took the advantages from the full-grown potential of Multimedia and 3D Animations. The main goal of this CD-ROM platform product is as a tool that will be able to teach the users what skeleton system is, its functions and know exactly how the bones look like in a very dynamic and interactive method.